2018
DOI: 10.1002/nau.23876
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐induced autonomic dysregulation of mitochondrial function in the rat urothelium

Abstract: Aim Chronic stress exacerbates the symptoms of most pain disorders including interstitial cystitis/bladder pain syndrome (IC/BPS). Abnormalities in urothelial cells (UTC) occur in this debilitating bladder condition. The sequence of events that might link stress (presumably through increased sympathetic nervous system‐SNS activity) to urothelial dysfunction are unknown. Since autonomic dysregulation, mitochondrial dysfunction, and oxidative stress all occur in chronic pain, we investigated whether chronic psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
(109 reference statements)
1
16
0
1
Order By: Relevance
“…In addition, this WAS‐induced bladder hypersensitivity was exacerbated by early life stress, 139 which could mimic the potential relationship between childhood relational affect dysregulation and the development of IC/BPS without Hunner lesions in humans 140 . Interestingly, a recent study reported the potential link between WAS‐induced chronic stress and urothelial dysfunction, which was mediated by autonomic mechanisms and mitochondrial malfunction 137,141 . Taken together, these models might facilitate the development of novel therapies and future research on the pathogenesis of IC/BPS without Hunner lesions.…”
Section: Animal Modelsmentioning
confidence: 94%
“…In addition, this WAS‐induced bladder hypersensitivity was exacerbated by early life stress, 139 which could mimic the potential relationship between childhood relational affect dysregulation and the development of IC/BPS without Hunner lesions in humans 140 . Interestingly, a recent study reported the potential link between WAS‐induced chronic stress and urothelial dysfunction, which was mediated by autonomic mechanisms and mitochondrial malfunction 137,141 . Taken together, these models might facilitate the development of novel therapies and future research on the pathogenesis of IC/BPS without Hunner lesions.…”
Section: Animal Modelsmentioning
confidence: 94%
“…All these compounds increase primarily the cytosolic Ca 2+ concentration, followed by mitochondrial ROS formation and eventually followed by apoptosis and cell death. But also psychosocial stress results in the increase of cytosolic Ca 2+ concentration, as shown in isolated cardiomyocytes [85], in platelets [86], hippocampal-derived HT22 cells [87], urothelial cells [88], and cardiomyocytes [89]. The neurotoxic effect of glutamate in neurons via the N-methyl-D-aspartat-receptor was related to an increase of cytosolic Ca 2+ and the formation of ROS [90,91].…”
Section: Stress and Calcium Signalingmentioning
confidence: 97%
“…Various stress signals were shown to increase cytosolic calcium concentrations in cells including high glutamate[ 94 ] or glucose[ 95 ]. In addition, psychosocial stress was shown to increase cytosolic calcium, as shown in cardiomyocytes[ 96 ], platelets[ 97 ], hippocampal-derived HT22 cells[ 98 ], urothelial cells[ 99 ], and cardiomyocytes[ 100 ]. Under resting conditions the cytosolic calcium concentration is low (about 0.1 micromolar), and a cAMP-dependent PKA rephosphorylates CytOx, accompanied by dimerization and switching on the allosteric ATP-inhibition of CytOx.…”
Section: Hypothesismentioning
confidence: 99%